Boundedness of the Generalized Riemann-Liouville Operator in Local Morrey-Type Spaces - Senouci, Mariam (Eurasian Mathematical Journal, 2023)
The objective is to establish the boundedness of the generalized multi-dimensional Riemann-Liouville integral operator from one local Morrey-type space to another under certain conditions on numerical parameters p and q.